Vozes infantis na escola: experiências e saberes sobre ciência a partir das culturas infantis - Dutra, Rosária Jordão (2019)
This work entitled: Children's voices in school: experiences and knowledge about science from children's cultures, aims to understand how the production of knowledge by children through their experiences with school. This time, we also try to highlight the process of authorship and cultural production by the children together with their peers, since the main idea of the research is to value it as a being that has its own knowledge. The research is configured as a phenomenological study that has as principle the essence of things and how they are perceived in the world. The theoretical-methodological support that guides the work is the Sociology of Childhood, with the understanding that children are producers of cultures and their attitudes are investigative. Having as central focus the consideration of children as social actors of law who can and should be participants in the investigative process, we request the authorization of their parents and children. Thirty-three children and one teacher participated as subjects in the study. The study was conducted at a municipal public school in the city of Manaus / AM. As methodological procedures we used participant observation and the children's graphic record, and the instruments of data collection were the voice recorder, photographic camera and the field diary to register the children with their peers. It was possible to verify that the production of knowledge of the children through their experiences with the school happens when we construct a space of listening in the classroom with them. We conclude that the recognition of children within these institutions still shows itself as a goal to be achieved by the educational and academic context.